Peningkatan produktifitas lebah madu melalui penerapan sistem integrasi dengan kebun kopi - Saepudin, R.; Fuah, A. Fuah M.; Sumantri, C.; Abdullah, L.; Hadisoesilo, S. (Faculty of Animal Science, Universitas Brawijaya, 2011)
Abstract : The study of relationship between the honey productivity and honey bee-coffee plantation integration was conducted in Kepahiang, the Province of Bengkulu. The objective of this study was to evaluate the application of Apis cerana-coffee plant integration system on honey production and coffee bean as well.. The experiment was arranged in a completely randomized design with two treatments and ten replications. The result showed that honey production was higher by 114% than that outside the plantation. Similar to the honey productionn, coffee been production at honeybee-coffee plantation integration was significantly higher by 10,55 % than that was unpollinated by Apis cerana.Key words: cerana, coffee, integration. production